2020
DOI: 10.5194/acp-2020-1075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure, dynamics, and trace gases variability within the Asian summer monsoon anticyclone in extreme El Niño of 2015–16

Abstract: Abstract. In this work, the detailed changes in the structure, dynamics and trace gases within the Asian summer monsoon anticyclone (ASMA) during extreme El Niño of 2015–16 is delineated by using Aura Microwave Limb Sounder (MLS) measurements, COSMIC Radio Occultation (RO) temperature, and NCEP reanalysis products. We have considered the individual months of July and August 2015 for the present study. The results show that the ASMA structure was quite different in 2015 as compared to the long-term (2005–2014) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The increase in ASR values may be attributed to the dry aerosols through nucleation processes [20]. In recent times, the increase in forest fires transports the pollutants to the ATAL region and enhances the aerosol concentration, which will have climate changes effects [4,42,43]. Thus, ISM activity plays an important role on the ASMA and, hence, on its tracers and aerosol distribution.…”
Section: Influence Of Asian Summer Monsoon Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in ASR values may be attributed to the dry aerosols through nucleation processes [20]. In recent times, the increase in forest fires transports the pollutants to the ATAL region and enhances the aerosol concentration, which will have climate changes effects [4,42,43]. Thus, ISM activity plays an important role on the ASMA and, hence, on its tracers and aerosol distribution.…”
Section: Influence Of Asian Summer Monsoon Activitymentioning
confidence: 99%
“…The ASMA is bounded by a westerly (easterly) jet in the north (south) side and prominent for a long duration of air confinement [3]. The location and shape of the ASMA vary at different time scales, i.e., inter-seasonal, inter-annual and longer time scales [2,4]. Previous studies reported the intensification and expansion of the South Asian High [5].…”
Section: Introductionmentioning
confidence: 99%